Transmission and emission terahertz time-domain spectroscopy with polarisation-sensitive photoconductive receivers - Castro-Camus, E; Lloyd-Hughes, J; Fu, L; Tan, H; Jagadish, C; Johnston, M; IEEE (2007)
In this contribution a detailed characterisation of the performance of three-contact polarisation-sensitive terahertz detectors will be discussed. Furthermore the appropriate mathematical formalism required for the analysis of polarisation-resolved THz measurements will be presented. In addition, measurements of the polarisation-resolved transmission of quartz and polarisation-resolved emission of (110) ZnTe will be shown in order to illustrate the relevance of polarisation in time domain measurements. Finally perspectives on experiments that require polarisation sensitivity will be discussed.